A Comparison of Properties Between Eco-Brick and Lightweight Brick by Using SolidWorks Software - Lim, Mei Chien; Roslinda Ali; Noraini Marsi (Progress in Engineering Application and Technology, 2022)
One of the most common construction materials used in building construction is brick. Even though there are many advantages of using brick in building construction, the production of brick also brings disadvantages to the environment and human health. Eco-brick has been identified as one of the instruments that can be used to replace the use of brick in construction. An eco-brick is a Polyethylene Terephthalate (PET) bottle filled up with mixed inorganic waste such as plastics, foams, packaging, and cellophane. The aim of this study is to investigate the characteristics and properties of an eco-brick as a replacement for a building block. Five samples of eco-bricks with different density ratios (0.15g/m3, 0.35g/m3, 0.55g/m3, 0.75g/m3, and 0.95g/m3 respectively) together with a lightweight brick control sample were prepared and tested by using SolidWorks software. The samples are tested by conducting the compressive strength test, drop test, and failure analysis. From the result, it can be said that the compressive strength of eco-brick increases as its density increases. In addition, as the density of eco-brick and the drop height increase, the impact strength of the eco-brick also increase. At the end of the study, it can be concluded that the eco-brick with a density ratio of 0.95g/m3 is the best and suitable to be used as a replacement brick because it gives the optimum strength in the compressive strength test and drop test compared to the conventional lightweight brick.